2001
DOI: 10.1002/jmv.2055
|View full text |Cite
|
Sign up to set email alerts
|

Resistance profile and cross‐resistance of HIV‐1 among patients failing a non‐nucleoside reverse transcriptase inhibitor‐containing regimen*

Abstract: The objectives were to determine the resistance profile and the rate of cross-resistance in HIV-1 infected patients failing an efavirenz or a nevirapine or a nevirapine then efavirenz containing regimens, and to investigate if zidovudine and more generally thymidine analog nucleosides lead to a particular genotypic pattern in nevirapine failing patients. A study was conducted in 104 patients with virological rebound to a non-nucleoside reverse transcriptase inhibitors (NNRTI) regimen (efavirenz n = 39, nevirap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
55
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(60 citation statements)
references
References 16 publications
5
55
0
Order By: Relevance
“…In fact, in all patients, viruses in plasma harbored NNRTI and NRTI resistance mutations (Table 1). These results agree with previous studies that have shown the quasisystematic presence of NNRTI resistance mutations associated with failure of NNRTI regimens (4,5,7). Viral load (Roche Amplicor HIV-1 Monitor assay 1.5), CD4 cell counts (flow cytometric analysis [Coulter]), and genotype (automated population-based full-sequence analysis [ABI System]) were determined at day 0 (the time of NNRTI interruption) and then at days 15, 30, and 60.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…In fact, in all patients, viruses in plasma harbored NNRTI and NRTI resistance mutations (Table 1). These results agree with previous studies that have shown the quasisystematic presence of NNRTI resistance mutations associated with failure of NNRTI regimens (4,5,7). Viral load (Roche Amplicor HIV-1 Monitor assay 1.5), CD4 cell counts (flow cytometric analysis [Coulter]), and genotype (automated population-based full-sequence analysis [ABI System]) were determined at day 0 (the time of NNRTI interruption) and then at days 15, 30, and 60.…”
supporting
confidence: 93%
“…According to these authors, mutations such as V106A, G190C/S/E/Q, P225H, M230L, and P236L can reduce replication capacity to various degrees. However, these mutations are not the most frequently selected or are usually associated with primary substitution in clinical context (4)(5)(6)(7). In fact, depending on the NNRTI compound used, primary mutations such as K103N, Y181C/I, Y188C, and G190A are the most common substitutions selected in NNRTI regimen failure (6).…”
mentioning
confidence: 99%
“…However, one major limitation of narrow-spectrum NNRTIs is that they have a low genetic barrier for resistance, and a single mutation, such as K103N, is able to cause cross-resistance to all the drugs in this class (12,18). Resistance to narrow-spectrum NNRTIs can develop quickly if low-grade HIV replication is permitted to occur, and this has spurred efforts to discover newer NNRTIs that have improved potency and a higher genetic barrier for resistance.…”
mentioning
confidence: 99%
“…However, the utility of the currently licensed NNRTIs is limited by the relatively easy selection of single mutations that alone can confer large reductions in susceptibility to the drug: i.e., they are characterized by a low genetic barrier to the development of resistance. This disadvantage is compounded by cross-resistance across the class (4,11), which makes sequential therapy with the currently licensed NNRTIs clinically inappropriate (3). Resistance to NNRTIs among HIV-1-positive patients receiving antiretroviral therapy is widespread, and the prevalence of transmitted NNRTI resistance is also increasing in some populations (14,17,26,33).…”
mentioning
confidence: 99%